From dilute isovalent substitution to alloying in CdSeTe nanoplatelets. Issue 22 (23rd May 2016) - Tenne, Ron; Pedetti, Silvia; Kazes, Miri; Ithurria, Sandrine; Houben, Lothar; Nadal, Brice; Oron, Dan; Dubertret, Benoit
Abstract : Synthesis and spectroscopy of CdSe x Te(1− x ) nanoplatelets going from the alloyed regime to dilute doping. Abstract : Cadmium chalcogenide nanoplatelet (NPL) synthesis has recently witnessed a significant advance in the production of more elaborate structures such as core/shell and core/crown NPLs. However, controlled doping in these structures has proved difficult because of the restrictive synthetic conditions required for 2D anisotropic growth. Here, we explore the incorporation of tellurium (Te) within CdSe NPLs with Te concentrations ranging from doping to alloying. For Te concentrations higher than ∼30%, the CdSe x Te(1− x ) NPLs show emission properties characteristic of an alloyed material with a bowing of the band gap for increased concentrations of Te. This behavior is in line with observations in bulk samples and can be put in the context of the transition from a pure material to an alloy. In the dilute doping regime, CdSe:Te NPLs, in comparison to CdSe NPLs, show a distinct photoluminescence (PL) red shift and prolonged emission lifetimes (LTs) associated with Te hole traps which are much deeper than in bulk samples. Furthermore, single particle spectroscopy reveals dramatic modifications in PL properties. In particular, doped NPLs exhibit photon antibunching and emission dynamics significantly modified compared to undoped or alloyed NPLs.